Lie symmetries of birational maps preserving genus 0 fibrations - Llorens, Mireia; Mañosa, Víctor (Journal of mathematical analysis and applications, 2015)
We prove that any planar birational integrable map, which preserves a fibration given by genus 0 curves has a Lie symmetry and some associated invariant measures. The obtained results allow to study in a systematic way the global dynamics of these maps. Using this approach, the dynamics of several maps is described. In particular we are able to give, for particular examples, the explicit expression of the rotation number function, and the set of periods of the considered maps.